1995
DOI: 10.1159/000119192
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine Use: is There a Net Benefit for Mood and Psychomotor Performance?

Abstract: We agree with the conclusions of a recent article in this journal [James, Neuropsychobiology l994;30:124–125] that studies on the psychoactive effects of caffeine need to take into account the possibility that the results obtained might represent merely the reversal of deleterious effects of caffeine deprivation rather than an actual net benefit due to caffeine use. However, in a review of recent studies we find no unequivocal evidence of impaired psychomotor performance associated with caffeine withdrawal. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
2
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(27 citation statements)
references
References 16 publications
1
23
2
1
Order By: Relevance
“…These results show clearly that overnight caffeine deprivation is sufficient to induce significant negative effects, including tiredness, headache and depressed mood. Although it is possible that pre-existing differences in personality or other factors unaffected by caffeine use could explain differences in mood between users and non-users (Smith et al 1991 ;Rogers et al 1995), this study also found that increased tiredness, drowsiness, anger and dejection were present in caffeine users after overnight caffeine deprivation but not after prolonged deprivation. In other words, the only factor which can reasonably account for the presence or absence of these particular symptoms is the subjects' recent history of caffeine consumption.…”
Section: Caffeinecontrasting
confidence: 44%
“…These results show clearly that overnight caffeine deprivation is sufficient to induce significant negative effects, including tiredness, headache and depressed mood. Although it is possible that pre-existing differences in personality or other factors unaffected by caffeine use could explain differences in mood between users and non-users (Smith et al 1991 ;Rogers et al 1995), this study also found that increased tiredness, drowsiness, anger and dejection were present in caffeine users after overnight caffeine deprivation but not after prolonged deprivation. In other words, the only factor which can reasonably account for the presence or absence of these particular symptoms is the subjects' recent history of caffeine consumption.…”
Section: Caffeinecontrasting
confidence: 44%
“…Brice et al(2001) suggests that caffeine increases alertness and reduces fatigue especially in low arousal situations [19] . Coffee has true performance-enhancing effects and at the same time, the existence of significant detrimental effects of caffeine deprivation on psychomotor performance has not been ruled out, confirms Rogers et al(1995) [20] .…”
Section: Coffee For Our Moodmentioning
confidence: 87%
“…As propriedades psicoestimulantes da cafeína, as característi-cas organolépticas da bebida e o ambiente social que, usualmente, acompanham o consumo de café, parecem contribuir como um todo para a manutenção do seu consumo. 14,53 Contudo, alguns indivíduos referem consumir café para evitar os sintomas de abstinência a ele associados. 51,54 Café e cefaleias A eficácia da cafeína no alívio das dores de cabeça induzidas pela sua privação (que leva à vasodilatação cerebral) reflecte as suas propriedades vasoconstritoras a nível central.…”
Section: 24unclassified